Germany's ancient pasts : archaeology and historical interpretation since 1700 - Maner, Brent (Chicago ; London : The University of Chicago Press, 2018)
The book offers a vivid portrait of the development of antiquarianism and archaeology, the interaction between regional and national history, and scholarly debates about the use of ancient objects to answer questions of race, ethnicity, and national belonging. While excavations in central Europe throughout the eighteenth and nineteenth centuries fed curiosity about the local landscape and inspired musings about the connection between contemporary Germans and their?ancestors,? antiquarians and archaeologists were quite cautious about using archaeological evidence to make ethnic claims. Even during the period of German unification, many archaeologists emphasized the local and regional character of their finds and treated prehistory as a general science of humankind. As Maner shows, these alternative perspectives endured alongside nationalist and racist abuses of prehistory, surviving to offer positive traditions for the field in the aftermath of World War II. A fascinating investigation of the quest to turn pre- and early history into history, Germany?s Ancient Pasts sheds new light on the joint sway of science and politics over archaeological interpretation.
Introduction -- The discovery of Germany's ancient pasts. The sources for prehistory: texts and objects in the eighteenth century -- Preparing artifacts for history: archaeology after the Napoleonic Wars -- Archaeology and the creation of historical places -- The new empire and the ancient past. Rudolf Virchow and the anthropological orientation of prehistory -- Domestic archaeology: a preeminently regional discipline -- Narrating the national past -- Between science and ideology. Professionalization and nationalism in domestic archaeology -- Prehistory as a national socialist narrative -- Epilogue.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed October 22, 2018).
eBooks on EBSCOhost
Keywords: Archaeology -- Germany -- History; Archaeology and history -- Germany; Archéologie -- Allemagne -- Histoire; Archéologie et histoire -- Allemagne; HISTORY -- Ancient -- General; Archaeology; Archaeology and history; Germany; antiquarianism; archaeology; museums; narration; nationalism; pre- and early history; regional history; Electronic books; History